(untitled) (Research, Society and Development, 2022)
In an extremely volatile environment, hotels seek improvements in the services and products on offer. This is mainly due to the competitiveness and competition experienced by the sector. The difficulty of those who integrate the segment to remain becomes their main concern. And, in the face of this, awakening strategic and competitive attitudes are necessary for the well-being and survival of the members of the sector in question. In this context, the objective of this study is to identify the tourist capabilities that effectively contribute to the competitive advantage of the hotel segment based on Tripadvisor data. Its methodology was to qualitatively analyze the evaluations of hotel service users who showed dissatisfaction with the accommodation experience and left their opinions on the Tripadvisor site. In the research, the Grounded Theory (GT) method was used in its second generation (Charmaz, 2006), and its locus was the Vila de Jericoacoara, located in the municipality of Jijoca de Jericoacoara. The treatment of data and indicators on tourism and accommodation in the village occurred through categorization, in favor of the use of Atlas TI and Iramuteq software. The content analysis technique was performed using information based on reviews made by guests who were more than dissatisfied with their accommodation. Based on the results presented, it was observed that the objective of the study was achieved, as it was possible to identify which tourist capabilities effectively contribute to the competitive advantage of hotel businesses, based on data collected at the online travel agency researched.